Komparasi Penerapan Metode Simple Additive Weighting Dengan Weighted Product Dalam Seleksi Trainer - Wahyuddin; Subandi Wahyudi; Ahmad Kautsar (JURNAL FASILKOM, 2021)
PT Chandra Asri Petrochemical Tbk (CAP) is the largest Polypropylene producer in Indonesia and was founded in 1984. For the sustainability of the company's operations, PT CAP constantly updates, both in the field of information technology and the capabilities of human resources within the company. Improving the ability of human resources in the field of information technology and aspects of information technology training (IT Training) is important to ensure that skilled human resources are ready to answer challenges in the use of information technology. In ensuring that trainers are selected to train human resources to be reliable and competitive, appropriate and accurate decisions are needed. The Simple Additive Weighting (SAW) and Weighted Product (WP) methods are methods that can be used in the decision-making process. The comparison of the two methods can help maximize the trainer selection decision-making process. The results of the implementation of the two methods are the same ranking order, the first rank in both methods is achieved by the third alternative. The final result obtained from the ranking process using the SAW (Simple Additive Weightingmethod)obtained the largest value as the best alternative with a value of 0.85. The final result obtained from the ranking process using the WP (methodWeighted Product)obtained the largest value as the best alternative with a value of 0.2308.